Impact of a respiratory panel on the diagnosis and management of acute chest syndrome in pediatric patients with sickle cell disease: A single-center retrospective study - Yaoping Zhang; Stelios Kasikis; Susannah Vanderpool; Paula Ogrodnik; Nikolaos Spyrou; Margaret R. Hammerschlag (Pediatric Hematology Oncology Journal)
Background: Acute chest syndrome (ACS) is a common sickle cell disease (SCD) complication. Infectious pathogens are the most common causes of ACS followed by pulmonary infarction and fat embolism. Infectious pathogens responsible for ACS include viruses and atypical bacteria (Mycoplasma pneumoniae and Chlamydia pneumoniae). The implementation of the BioFire® FilmArray® Respiratory Pathogen Panel (RPP) at our institution since 2017 provided an opportunity to more accurately investigate the infectious pathogens responsible for ACS in children with SCD. Material and methods: This study was a single-center retrospective review of electronic medical records of children with SCD, less than 21 years of age, who were admitted with a diagnosis of ACS. Results: Nighty-five episodes of ACS in 64 patients admitted to our hospital from January 2013 to March 2021 were identified. Episodes were assigned to pre-RPP (n = 50) and RPP (n = 45) cohorts. Within the RPP cohort, an infectious etiology was identified in 44 % (20/45) of episodes compared to 18.75 % (3/16) of the pre-RPP cohort. The two most common pathogens identified were rhino/enterovirus and influenza, found in 11 % of episodes each. M. pneumoniae was identified in only 2 episodes in the RPP cohort. Conclusion: Implementation of the RPP enabled more accurate identification of the causes of ACS. The majority of cases were due to viral infections. Pneumococcal and M. pneumoniae infections were uncommon. Based on these findings we suggest that empiric antibiotic be limited to ceftriaxone. Azithromycin should only be used if the RPP is positive for M. pneumoniae or C. pneumoniae.